A Cultural Study of the Dastan ’Sab Ras" - Syed Afaq Zahir (Journal of Religion and Society, 2025)
The Dastan Sab Ras, authored by Mulla Wajhi in the seventeenth century, is a landmark in the evolution of Urdu prose and one of the earliest examples of the classical dastan tradition in the Deccan. More than a work of fiction, it serves as a cultural mirror reflecting the socio-political, religious, and aesthetic life of its time. Written during the rule of the Qutb Shahi dynasty in Golconda, Sab Ras incorporates elements of romance, adventure, morality, and allegory while also preserving valuable ethnographic details of the Indo-Persian cultural synthesis characteristic of the Deccan courts. A cultural study of Sab Ras reveals a nuanced depiction of contemporary norms, traditions, and values. It portrays royal etiquette, courtly pleasures, festivals, trade activities, clothing styles, and culinary practices, while also documenting the spiritual and moral ethos of seventeenth-century Indo-Muslim society. The text reflects a harmonious fusion of Islamic and indigenous Indian customs, demonstrating how cultural exchange enriched literature and daily life in the Deccan. The author’s use of language, infused with Persian and Arabic vocabulary alongside local idioms, provides insight into the linguistic texture of the time. The narrative is replete with moral teachings, symbolic characters, and allegorical episodes that underscore virtues such as justice, generosity, loyalty, and piety, while also warning against greed, arrogance, and betrayal. Descriptions of processions, celebrations, and architectural marvels evoke the grandeur of the Qutb Shahi court, while domestic scenes and depictions of social gatherings bring everyday culture vividly to life. By intertwining entertainment with cultural documentation, Sab Ras stands as both a literary and historical source, preserving details of political hierarchy, gender roles, and artistic expression. This study positions the dastan not merely as an imaginative creation but as a vital record of a composite Indo-Islamic civilization, bridging the worlds of literature, history, and anthropology. Keywords: Urdu Dastan, Sab Ras, Mulla Wajhi, Deccan Literature, Indo-Persian Culture, Qutb Shahi Dynasty, Seventeenth Century, Cultural History, Courtly Traditions, Social Customs